Bank enforcement actions and the terms of lending - Yota Deli; Manthos D. Delis; Iftekhar Hasan; Liuling Liu (Bank of Finland, 2016)
Formal enforcement actions issued against banks for violations of laws and regulations related to safety and soundness can theoretically have both positive and negative effects on the terms of lending. Using hand-collected data on such enforcement actions issued against U.S. banks, we show that they have a strong negative effect on price terms (loan spreads and fees) for corporate loans and a positive one on non-price terms (loan maturity, size, covenants, and collateral). The results also indicate that in the absence of enforcement actions, the cost of borrowing during the subprime crisis would have been much higher, while punished banks intensify use of collateral.
URN:NBN:fi:bof-201608121373
Keywords: E44; E51; G21; G28; 330